Dentistry: its Role in the Transmission of SARS-CoV-2 Through Bioaerosols - Rodríguez Aguilar, Reinaldo (Odovtos - International Journal of Dental Sciences, 2020)
Dental practice faces the paradigm shift and the modification of protocols in biosafety, an aspect that has become a variable to be practiced by each professional as part of their conduct at all times in order to survive as a profession in the face of the global pandemic that it represents the risk of transmission of the new coronavirus called COVID-19. One of the most important problems in dental biosecurity is represented by the generation of bioaerosols, since these are vectors that transport microorganisms to inside people’s bodies, which generates a potential occupational risk already known in the dental sciences but that it is enhanced with the transmissibility and pathogenicity of the new coronavirus. Until now, there are many questions about transmission through aerosols of SARS-CoV-2 , so the general objective of this review is to understand the scientific elements that govern the aerodynamics of bioaerosols applied to the dental environment and how these can become a potential virus disseminator when intraoral dental procedures are performed in infected patients. Understanding the aerodynamics of bioaerosols helps us understand how SARS-CoV-2 present in bioaerosol generated by dental procedures in infected patients can vary in terms of viability and infectivity by influencing other factors such as relative humidity, room temperature, air currents, bioaerosol physicochemical factors and the host´s immune system.